2014
DOI: 10.1068/a130348p
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Family Nexus: An Analytical Tool in Considering Community/m-MGO Haritika's Ties in Bundelkhand, Central India

Abstract: H aritika, M aanpura, N ear Com m unity solar pow er plant, M ahoba Road, N ow gong, D istrict C hhatarpur M adhya Pradesh, India; Abstract. In this paper we apply the notion of the amorphous family nexus (AFN) to examine the underinvestigated implications of family-like ties existing between minor NGOs (m-NGOs) and communities in sustaining the momentum of developmental activities despite resource scarcity and weak institutional support. AFN embodies symbolic connectedness and meaningful associations that act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…For women, reasons such as not being taken seriously in the meetings, inconvenient timings of the meetings and lack of information about the meeting are prominent across the villages. The patriarchal structure of the villages also became evident with the finding that about 11.4% of women in Chhatpur and 10.2% in Parasai could not attend the meetings due to lack of support from family members (Kumar & Kumar, 2022;Saxena & Singh, 2014 Women participants from non-dominant communities particularly believed that their concerns were not adequately addressed either in the WC or village association meetings. One of the key informants from Bacchauni village observed that a part of her family landholding is submerged under water after the construction of the watershed until the festival of Deepawali in November.…”
Section: Resultsmentioning
confidence: 99%
“…For women, reasons such as not being taken seriously in the meetings, inconvenient timings of the meetings and lack of information about the meeting are prominent across the villages. The patriarchal structure of the villages also became evident with the finding that about 11.4% of women in Chhatpur and 10.2% in Parasai could not attend the meetings due to lack of support from family members (Kumar & Kumar, 2022;Saxena & Singh, 2014 Women participants from non-dominant communities particularly believed that their concerns were not adequately addressed either in the WC or village association meetings. One of the key informants from Bacchauni village observed that a part of her family landholding is submerged under water after the construction of the watershed until the festival of Deepawali in November.…”
Section: Resultsmentioning
confidence: 99%